PTU-106 Successful Pregnancies With Thiopurine-allopurinol Co-therapy For Inflammatory Bowel Disease. (9th June 2014) - Sheikh, M; Nelson-Piercy, C; Stenner, J; Mackenzie, G; Duley, J; Florin, T; Ansari, A
Abstract : Introduction: Combination of low dose thiopurine with allopurinol can improve the clinical efficacy and bypass some of the adverse reactions of thiopurine monotherapy. Thiopurines can be used safely during pregnancy but there is scarce data regarding allopurinol. We report twelve cases of safe use of thiopurine and allopurinol co-therapy to manage IBD during pregnancy. Methods: Patients were retrospectively identified at two hospitals in the UK and in Australia, using our local IBD databases. All pregnancies of co-therapy patients were included. TPMT activity and pre-pregnancy weight were used to calculate thiopurine dosing. Data regarding pregnancy and fetal outcomes were collected from patient notes. Results: Eleven females on co-therapy became pregnant, totalling twelve pregnancies with eight live births (Table 1 ) and four ongoing pregnancies. There were no reported terminations, miscarriages or spontaneous pre-term deliveries (<37 weeks). Four patients gave birth by spontaneous vaginal delivery (SVD); four by Caesarean section (C-section). There were no low birth weight (<2.5kg) babies. The APGAR scores of all babies were normal and no congenital malformations were identified either on fetal ultrasound scans or on neonate checks. The median duration of follow-up of babies was 6.5 months with no indication of morbidity. Conclusion: All twelve cases were treated successfully with co-therapy without any adverse pregnancy related events or adverse fetal outcomes. Intrauterine exposure of the fetus to thiopurine metabolites is not greater with combination therapy compared with thiopurine monotherapy. There are only two reports of congenital malformations with maternal allopurinol use. The case for an association based on two cases is weak, moreover a negative publication bias with respects to successful maternal allopurinal use is suspected. Our study provides support for clinicians and patients wishing to continue thiopurine-allopurinol co-therapy during pregnancy. Disclosure of Interest: None Declared.